On algebras associated to partially ordered sets - Brun, Morten; Römer, Tim (MATHEMATICA SCANDINAVICA, 2008)
We continue the work [2] on sheaves of rings on finite posets. We present examples where the ring of global sections coincide with toric faces rings, quotients of a polynomial ring by a monomial ideal and algebras with straightening laws. We prove a rank-selection theorem which generalizes the well-known rank-selection theorem of Stanley-Reisner rings. Finally, we determine an explicit presentation of certain global rings of sections.